Impact of Seepage on the Underground Water Level in a Complex Soil-Water-Structure System. (6th December 2022) - Li, Youfeng; Mu, Linlong; Cao, Jie
Abstract : The antifloating design of underground structures is very important in areas with high underground water levels, and reasonable evaluation of the buoyancy is based on accurately describing the distribution of the groundwater level. However, the natural groundwater flow would be disturbed by the structure, which is not considered in the antifloating design. In the present paper, the influence of the width of an underground structure on the groundwater level in homogeneous soil is investigated through an indoor physical model test in the first place, which serves as a benchmark for the numerical simulation. Then, the parametrical study is carried out with numerical simulation. The results show that the width of the structure has the greatest influence on the water level around the structure, followed by the influence of the insertion depth, whereas the length has little influence. The hydraulic gradient has a significant effect on that as well. Moreover, the hydraulic conductivity ratio between different soil layers also affects the water level magnitude. Based on the results, a prediction method for the groundwater level around the structure for both homogeneous soil and multilayer soil has been developed and evaluated.